ALGUNOS PARTICULARIDADES DEL HIGADO DEL ELEFANTE - VILLASENOR CASTELLANOS, C (Laboratorio de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1942)
This study, 4th of a series, investigates several types of modification of the pure reflex, conditioned in the sense of Pavlov and of Sherrington Cats anaesthetized with chloral and with dial were the experimental material; electrical stimulation was app
BOL INST ESTUD MED BIOL
Keywords: PARTICULARIDADES, HIGADO, ELEFANTE; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL; ZOOLOGIA GENERAL